2020
DOI: 10.1111/crj.13306
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstructive sleep apnoea in final year medical students and junior doctors‐a multi‐centre cross‐sectional study

Abstract: Background Sleep medicine is an under‐recognised medical specialty in Pakistan and obstructive sleep apnoea (OSA) often goes unnoticed. Final year medical students and junior doctors are the primary medical contact to elicit patient history and physical examination. We aimed to measure the current knowledge of OSA amongst the final year medical students and junior doctors at four university teaching hospitals across three large Pakistani cities. Methods Cross‐sectional survey of final year medical students and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Similar studies which have used OSAKA-KIDS elsewhere reported higher knowledge levels of physicians about pediatric OSA (58.3–66.7%) [ 15 , 27 ] than that reported in the present study (30.5%). Many studies have reported lower knowledge levels of medical students and graduates about OSA than experienced doctors and specialists using the OSAKA questionnaire [ 15 , 21 , 22 , 23 , 24 , 25 , 27 , 31 , 32 ]. One of those studies reported that knowledge of physicians about pediatric OSA lagged behind that of adults [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies which have used OSAKA-KIDS elsewhere reported higher knowledge levels of physicians about pediatric OSA (58.3–66.7%) [ 15 , 27 ] than that reported in the present study (30.5%). Many studies have reported lower knowledge levels of medical students and graduates about OSA than experienced doctors and specialists using the OSAKA questionnaire [ 15 , 21 , 22 , 23 , 24 , 25 , 27 , 31 , 32 ]. One of those studies reported that knowledge of physicians about pediatric OSA lagged behind that of adults [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of those studies reported that knowledge of physicians about pediatric OSA lagged behind that of adults [ 27 ]. This can be attributed to the lack of experience of students and fresh graduates [ 21 , 22 ]. Limited exposure to both didactic and clinical training about pediatric OSA in the undergraduate curricula is another important factor, particularly after considering that around half of the participants in this study (45.4%), regardless of the college type, were unaware if their curriculum included information about pediatric OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed to assess the knowledge of OSA among medical professionals using OSAKA questionnaire have obtained variable results revealing the gap in the knowledge and awareness regarding OSA. [12][13][14] Experienced doctors and specialists have yielded higher score while interns, recent graduates and medical students have got lower score. 12,15,18 In the present study, the respondents obtained mean total knowledge of 9.75 out of 18.…”
Section: Discussionmentioning
confidence: 99%
“…3,[7][8][9][10][11] It was observed that in four university teaching hospitals, final year medical students and junior doctors had limited knowledge about the OSA diagnosis and management. 12 Wadhwa et al also reported poor knowledge among medical undergraduates about OSA. 13 Another recent study done in Nigeria also documented poor knowledge of OSA among medical doctors.…”
Section: Introductionmentioning
confidence: 99%